Breastfeeding Practices among Native Hawaiians and Pacific Islanders - Ingrid K. Richards Adams; Chizimuzo T. C. Okoli; Akilah Dulin Keita; Ana Maria Linares; Keiko Tanaka; Joshua R. Polanin; Annie Koempel (Journal of Obesity)
Background. Breastfeeding is associated with a decreased risk of obesity in the early and adult years. Native Hawaiians and Pacific Islanders (NHPI) experience high rates of obesity which is often obfuscated with aggregated data. Using disaggregated data, we examined breastfeeding practices among NHPI. Methods. Seven databases and reference lists were searched. Two independent researchers extracted relevant studies based on predetermined criteria. Nine studies met our inclusion criteria and a meta-analysis was conducted using random-effects, inverse-various weighted models. Results. Few studies disaggregated NHPI populations when examining breastfeeding practices. Most studies were cross-sectional and our search yielded no randomized or quasirandomized control trials. The results of the meta-analysis indicated that 46.5% NHPI women initiated breastfeeding with 40.8% breastfeeding exclusively. These pooled analyses show that NHPI breastfeeding practices are below the recommended national and international goals and guidelines. Conclusion. Breastfeeding practices among NHPI are heterogeneous and critical disparities exist among certain NHPI subgroups and additional research needs to be conducted to determine the reasons for the disparity. Future studies should work to disaggregate data for NHPI and the various subpopulations. Multicomponent, multilevel strategies are needed to support breastfeeding practices among NHPI.